The Technologies of the Future in the Field of Fertilisers and Romania’s Opportunities to Recover this Industry - Cristian Moisoiu; Constantin Ciupagea; Ștefan-Radu Oprea; Răzvan Pîrcălăbescu (Amfiteatru Economic)
The fertiliser industry in the European Union is undergoing structural transformations imposed by EU commitments to become carbon neutral by 2050. In terms of the existing possibilities, the industry is in the attention of decision-makers and investors, with various business models being analysed that enable technologies of the fourth industrial revolution that will improve the efficiency of manufacturing of fertilisers necessary for sustainable agriculture, with the reduction of carbon dioxide emissions. The present paper aims to analyse the evolution of the fertiliser industry in Romania, in terms of international competitiveness and economic performance of companies, as well as to evaluate the existing possibilities for modernising and recovering the industry. These analyses and evaluations can provide a basis for formulating recommendations to decision-makers in reindustrialisation policies, taking into account new technologies that can capitalise on the resources and opportunities of the regional market, while maintaining or intensifying the policies undertaken to decarbonise the energy-intensive industries.